Protocol for a multicenter, double-blind, randomized, placebo-controlled phase III trial of the inhaled β2-adrenergic receptor agonist salbutamol for transient tachypnea of the newborn (the REFSAL trial) - Madajczak, Dariusz; Daboval, Thierry; Lauterbach, Ryszard; Łoniewska, Beata; Błaż, Witold; Szczapa, Tomasz; Sadowska-Krawczenko, Iwona; Michalak-Kloc, Marzena; Sławska, Helena; Borszewska-Kornacka, Maria; Bokiniec, Renata; , the REFSAL Study Group (Frontiers in Pediatrics, 2023)
Background Transient tachypnea of the newborn (TTN), which results from inadequate absorption of fetal lung fluid, is the most common cause of neonatal respiratory distress. Stimulation of β-adrenergic receptors enhances alveolar fluid absorption. Therefore, the β2-adrenergic receptor agonist salbutamol has been proposed as a treatment for TTN. This study aims to evaluate the efficacy and safety of salbutamol as supportive pharmacotherapy together with non-invasive nasal continuous positive airway pressure (NIV/nCPAP) for the prevention of persistent pulmonary hypertension of the newborn (PPHN) in infants with TTN. Methods and analysis This multicenter, double-blind, phase III trial will include infants with a gestational age between 32 and 42 weeks who are affected by respiratory disorders and treated in eight neonatal intensive care units in Poland. A total of 608 infants within 24 hours after birth will be enrolled and randomly assigned (1:1) to receive nebulized salbutamol with NIV or placebo (nebulized 0.9% NaCl) with NIV. The primary outcome is the percentage of infants with TTN who develop PPHN. The secondary outcomes are the severity of respiratory distress (assessed with the modified TTN Silverman score), frequency of need for intubation, duration of NIV and hospitalization, acid–base balance (blood pH, partial pressure of O2 and CO2, and base excess), and blood serum ionogram for Na+, K+, and Ca2+. Discussion The Respiratory Failure with Salbutamol (REFSAL) study will be the first clinical trial to evaluate the efficacy and safety of salbutamol in the prevention of persistent pulmonary hypertension in newborns with tachypnea, and will improve short term outcomes. If successful, the study will demonstrate the feasibility of early intervention with NIV/nCPAP together with nebulized salbutamol in the management of TTN. Ethics and dissemination The study protocol was approved by the Bioethics Committee of the Medical University of Warsaw, Warsaw, Poland on November 16, 2020 (decision number KB/190/2020). All procedures will follow the principles of the Declaration of Helsinki. The results of the study will be submitted for knowledge translation in peer-reviewed journals and presented at national and international pediatric society conferences. Trial registration It is registered at ClinicalTrials.gov NCT05527704, EudraCT 2020-003913-36; Protocol version 5.0 from 04/01/2022